ASPEK-ASPEK SOSIAL DALAM NOVEL KUKUL BULUS KARYA NYOMAN MANDA - Agus Gunawan, I Wayan (Humanis; Volume 10. No 2. Februari 2015)
This study reviews the literature of modern Balinese novel titled novel manifold Kukul Bulus. This novel tells the story of the king and the people's struggle in defense of Badung Badung of oppression and attacks carried Netherlands. The purpose of this study was to determine the social aspects contained in the novel Kukul Bulus. This study uses the theory of literary sociology. Methods and techniques used in this study consists of three stages, namely the stage of providing data, data analysis stage and the stage presentation of the results of the data analysis. At this stage of the provision of the data used refer to the method supported with translation and recording techniques. At the stage of data analysis used qualitative methods and analytic descriptive techniques. The last stage is the stage presentation of the results of data analysis using informal methods and supported by deductive and inductive techniques. The results of this study are unfolding social aspects contained in the novel Kukul Bulus include: aspects of the struggle, romance aspects, historical aspects, aspects of loyalty, heroism aspects, and aspects of religion.
Keywords: novel, sociology, kukul bulus